Clinical Effects of Kinesio-taping on Shoulder Pain in Patients with Spastic Hemiplegia after Stroke - Wenlin SUN; Qiong YI; Min LU; Yu HAN; Yang LIU; Xiaowen SHEN; Guangxu XU (康复学报)
Objective:The aim of this study is to analysialysis clinical effects of different kinesio-taping on shoulder pain in patients with spastic hemiplegia after stroke.Methods:One hundred twenty patients from Rehabilitation Department with shoulder pain in spastic hemiplegia after stroke were randomly divided into observation group, control group and blank group, with 40 cases in each group. All patients received routine rehabilitation intevation. The control group was treated with the deltoid muscle and serratus anterior muscle (routine kinesio-taping), while the observation group was treated with the supraspinatus muscle, rhomboid muscle and superior trapezius muscle (new kinesio-taping). The curative effects were observed after 1 month. Patients in the blank group were not affected by kinesio-taping.Results:After one month of treatment, VAS scores were improved by (3.4±0.2) in the control group and (4.9±0.3) in the treatment group (P<0.01). The improvement amplitude of painless PROM was (23±0.8) °in the control group and (42±1.4) °in the treatment group. The comparison was statistically significant (P<0.01). The pain and activities of patients in the treatment group were better than those in the control group. VAS scores and painless PROM both in the treatment group and the control group were significantly better than those in the blank group (P<0.01). There were no significant differences of FMA scores and modified Ashworth scores in the treatment group and the control group compared with those in the blank group (P>0.05).Conclusion:The new method of kinesio-taping on shoulder pain has a significant effect on improving the function of patients with stroke during spasticity. But kinesio-taping therapy is short and unstable, and the long-term effect may be poor. During the spasticity period, the muscle tension of limbs keeps increasing, and the muscle strength grows slowly. In a short time, kinesio-taping and training have little effect on the motor function and muscle tension of the upper limbs.